Dravet Syndrome: An Electroclinical, Genetic, Treatment, and Outcome Study of 35 Patients in Argentina - Caraballo, Roberto H.; Veneruzzo, Gabriel; Loos, Mariana; Reyes, Gabriela; Juanes, Matías; Martín, Eugenia; Melgarejo Duarte, Sergio; Touzón, María Sol; Alonso, Cristina (Journal of Pediatric Epilepsy, 2024)
We analyzed the electroclinical features, molecular findings, treatment, disease course, and outcomes of patients with Dravet syndrome (DS) with positive genetic markers seen at a public hospital in Argentina. A retrospective study was conducted assessing the clinical records of 44 patients who met the diagnostic criteria for DS according to the 2022 classification of epilepsy of the International League Against Epilepsy seen at our center between March 2018 and June 2023. Of 44 patients, 35 (18 males and 17 females), in whom genetic studies yielded positive results, were included. Median age was 9 years (range 4 to 16 years), and the median time of follow-up was 10 years (range 3 to 14 years). The mean age at onset was 7 months. The first seizure was associated with febrile illness in all patients, and in 11 (31.4%), seizures were immediately preceded by either infectious disease or vaccination. Heterozygous pathogenic/likely pathogenic SCN1A variants were detected in 32 of the original 44 patients (73%), of which 47% were novel. Variants in other genes related to DS (HCN1, STXB1, and SCN1B) were identified in three patients. Cognitive delay and motor impairment were found to be more severe in patients that had multiple and drug-resistant seizures and in those who had the complete phenotype with myoclonic seizures. Novel SCN1A gene variants were identified in nearly half of the patients. The prognosis for cognitive development is unfavorable. Seizures are not well controlled with antiseizure medications and early treatment with ketogenic dietary therapy as well as cannabidiol should be considered.
Keywords: Dravet syndrome; genetic etiology; electroclinical features; outcome; treatment; SCN1A